2001
DOI: 10.1177/14746514010010010701
|View full text |Cite
|
Sign up to set email alerts
|

The HOPE Study and MICRO-HOPE Substudy

Abstract: BackgroundA CE inhibitors have a special role in diabetes care. They have been proven to reduce urinary albumin excretion and reduce the rate of progression of diabetic nephropathy and retinopathy. 1-3 There is proven benefit post myocardial infarction, with a greater beneficial effect in patients with diabetes in comparison to those without. 4 The effect of ACE inhibitors in patients who have low ejection fractions or overt cardiac failure is well described. 5 More recent studies indicate other benefits of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Marked differences in arterial and venous oxygen saturation levels and in arteriovenous difference were found between patients with and without sartan therapy. In the past, numerous studies dealt with the positive effects of ACE inhibitors and AT-II antagonists on possible cardiovascular outcomes 21 . The Heart and Outcomes Prevention Evaluation (HOPE) study confirmed vasculoprotective effects arising from treatment with ramipril.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marked differences in arterial and venous oxygen saturation levels and in arteriovenous difference were found between patients with and without sartan therapy. In the past, numerous studies dealt with the positive effects of ACE inhibitors and AT-II antagonists on possible cardiovascular outcomes 21 . The Heart and Outcomes Prevention Evaluation (HOPE) study confirmed vasculoprotective effects arising from treatment with ramipril.…”
Section: Discussionmentioning
confidence: 99%
“…Marked differences in arterial and venous oxygen saturation levels and in arteriovenous difference were found between patients with and without sartan therapy. In the past, numerous studies dealt with the positive effects of ACE inhibitors and AT-II antagonists on possible cardiovascular outcomes [21]. The Heart ▶ Table 2 Medians of the venous oxygen saturation, arterial oxygen saturation and the AV difference for the different degrees of severity of nonproliferative diabetic retinopathy and for proliferative diabetic retinopathy.…”
Section: Sartansmentioning
confidence: 99%
See 1 more Smart Citation
“…The prodiabetic effect of some β-blockers is concerning since diabetes increases the risk of adverse cardiovascular outcomes in hypertensive patients (Heart Outcomes Prevention Evaluation (HOPE) Study Investigators 2001; UK Prospective Diabetes Study (UKPDS) Group 1998). Studies have shown that patients being treated with β-blockers have as much as 32 % higher risk of developing diabetes when compared with individuals taking no drugs (Gress et al 2000; Messerli et al 2008).…”
Section: Introductionmentioning
confidence: 99%